Development of Smart Farming Technology on Ginger Plants in Padamulya Ciamis Village, West Java, Indonesia - Aceng Sambas; Mujiarto Mujiarto; Gugun Gundara; Gunawan Refiadi; Neneng Sri Mulyati; Ibrahim Mohammed Sulaiman (International Journal of Research in Community Services, 2023)
In this paper, we present a comprehensive study aimed at enhancing the cultivation of ginger plants through the integration of smart farming technology. Ginger (Zingiber officinale) is an essential crop in the agriculture-based economy of Indonesia, providing numerous health benefits and culinary applications. However, traditional farming methods often face challenges such as inefficiencies, resource wastage, and unpredictable yields. The research conducted in Padamulya Ciamis Village seeks to address these issues by harnessing the potential of smart farming technology. The study involves the implementation of cutting-edge agricultural tools, including Internet of Things (IoT) devices, sensor networks, and data analytics. By utilizing these advancements, the project aims to optimize the cultivation process, ensure sustainable resource management, and enhance overall productivity. The methodology of the research encompasses a mix of experimental trials, data collection, and analysis. Smart sensors are deployed to monitor critical variables such as soil moisture, temperature, humidity, and light intensity, enabling farmers to gain real-time insights into their ginger fields. The collected data is processed using machine learning algorithms, providing predictive models and personalized recommendations for cultivation practices. The results of this study demonstrate promising advancements in ginger farming practices. By implementing smart farming technology, farmers in Padamulya Ciamis Village experience optimized irrigation schedules, precise nutrient delivery, and timely pest control measures, leading to increased crop yields and improved quality. Furthermore, resource utilization efficiency is enhanced, minimizing water and fertilizer wastage, contributing to the sustainable and eco-friendly management of ginger plantations. Beyond its local implications, this research showcases the potential of smart farming technology as a transformative force in agriculture. The findings serve as a foundation for scaling up similar projects in other regions of Indonesia and beyond, contributing to the nation's agricultural modernization and food security. Finally, the development of smart farming technology on ginger plants in Padamulya Ciamis Village presents a promising pathway towards sustainable and efficient agricultural practices. By combining traditional farming knowledge with cutting-edge technology, this study exemplifies how smart farming can elevate crop cultivation, empower farmers, and foster rural development in Indonesia.